Hepatitis A and E among immigrants and refugees in Central Brazil - Grazielle Rosa da Costa e Silva; Thaynara Lorrane Silva Martins; Carla de Almeida Silva; Karlla Antonieta Amorim Caetano; Megmar Aparecida dos Santos Carneiro; Bruno Vinicius Diniz e Silva; Leonora Rezende Pacheco; Livia Melo Villar; Vanessa Salete de Paula; Regina Maria Bringel Martins; Sheila Araújo Teles (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To estimate the prevalence of hepatitis A virus (HAV) and hepatitis E virus (HEV) among immigrants and refugees in Goiás, Central Brazil. METHODS Overall, 355 individuals were interviewed, and blood samples were tested for anti-HAV and anti-HEV IgG. Anti-HEV-positive samples were similarly tested for HEV RNA. RESULTS All participants were from Latin American countries, most of whom, young adult males. The overall anti-HAV IgG prevalence was 87.4% (95%CI: 83.5-90.4), of whom 94.9%, 75.6%, and 60% were from Haiti, Venezuela, and other Latin American countries, respectively (p < 0.001). Age above 19 years and more than 36 months residing in Brazil were associated with a higher prevalence of previous HAV and HEV infection, respectively. Of the children eligible for HAV vaccination according to the National Immunization Program, only eight (44%) had been vaccinated. The overall anti-HEV IgG prevalence was 6.5% (95%CI: 4.4-9.5). All anti-HEV IgG-positive individuals were Haitians, including a child born in Brazil. HEV RNA was detected in two of the anti-HEV IgG-positive samples. CONCLUSION The survey detected a high prevalence of anti-HAV and anti-HEV IgG among immigrants and refugees, and active HEV infection among some Haitian participants. Prevention measures are urgently required to interrupt enteric virus transmission in this emergent and vulnerable population.